Optimizing Combined Emission Economic Dispatch for Solar Integrated Power Systems - Khan, Naveed Ahmed; Sidhu, Guftaar Ahmad Sardar; Gao, Feifei (IEEE access, 2016)
The dispatch of power at minimum operational cost of thermal energy sources has been a significant part of research since decades. Recently, with increasing interests in renewable energy resources, the optimal economic dispatch has become a challenging issue. This paper presents combined emission economic dispatch model for a solar photo voltaic integrated power system with multiple solar and thermal generating plants. We formulate mixed integer binary programming problem subject to various practical constraints. A decomposition framework is proposed where the original problem is split into two sub-problems. Particle swarm optimization, Newton-Raphson method, and binary integer programming techniques are exploited to find the joint optimization solution. The proposed model is tested on the IEEE 30 bus system. The simulation results demonstrate the effectiveness of the proposed model.